Uncover your risk! Using Facebook to increase personal risk awareness and screening of type 2 diabetes in Indonesia - Manuela Fritz; Michael Grimm; Ingmar Weber; Elad Yom-Tov; Benedictus Praditya (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2022)
We assess whether social media - in particular Facebook - can serve as an efficient and costeffective instrument to increase type 2 diabetes awareness and encourage risk screening activities in Indonesia, where - as in the rest of Southeast Asia - the prevalence of the disease and with it the rates of undiagnosed cases have dramatically increased in the last decade. We use Facebook's advertisement function to randomly distribute graphical ads related to the risk and consequences of diabetes to Facebook users above the age of 35 in Jakarta and Yogyakarta. The ads differ in their message ("theme") and graphical design, but equally invite viewers to visit an information website on which they can participate in a diabetes self-screening activity. Depending on their determined risk score, participants receive a recommendation to contact their GP and ask for an in-depth screening. We find that the ad themes that we label "information" and "shock" outperform all other themes in terms of creating link clicks and completed screening questionnaires. A follow-up survey six weeks after the online screening suggests that approximately 28% of respondents that were found to have a high risk, plan to schedule (or already have scheduled) an appointment for a professional screening. The complementary costeffectiveness analysis shows that such an online public health campaign can be very cost-effective with a cost of approximately US9 per newly diagnosed person with type 2 diabetes.
Keywords: I10; I12; I18; D83; D91; 330; health; diabetes; Facebook; screening; cost-effectiveness; Indonesia